The triple whammy anxiety depression and osteoarthritis in long-term conditions. Issue 1 (December 2015) - Tan, Valerie; Jinks, Clare; Chew-Graham, Carolyn; Healey, Emma; Mallen, Christian
Abstract Improving the management of people with long-term conditions is a key priority of the UK National Health Service. Whilst the coexistence of two or more long-term conditions in one person is increasingly the norm in primary care, guidelines and delivery of care remain focused on single disease management. Anxiety, depression and osteoarthritis are frequently comorbid with other long-term conditions and with each other, with up to 70 % of people with anxiety and depression also suffering from chronic pain. The relationships between anxiety, depression and pain are reciprocal, with each predicting and worsening the outcome of the others. Where these conditions occur in the context of other long-term conditions, further reduction in health-related quality of life and poorer clinical outcomes for all comorbid conditions is observed. It therefore follows that optimising the management of one comorbid condition should confer benefit to the other/s. Yet despite this, anxiety, depression and chronic pain are seldom prioritised by either patient or clinician, therefore remaining under-recognised and under-treated. Case-finding aims to identify and offer timely treatment to individuals with a given disease in a population at risk, therefore offering one possible solution. Yet case-finding is not without its problems, with well-recognised barriers including lack of time, cultural difficulties and inadequate resources and practitioner skills. So whilst the merits of why to actively seek these conditions is clear, how this may be best achieved is not. We explore the potential role of case-finding for anxiety, depression and osteoarthritis-related joint pain in individuals with comorbid long-term conditions, assessing whether adopting an integrated approach to care may allow opportunistic case-finding therefore promoting identification and timely management of these deleterious conditions.